2017
DOI: 10.1111/anec.12455
|View full text |Cite
|
Sign up to set email alerts
|

Automated T‐wave analysis can differentiate acquired QT prolongation from congenital long QT syndrome

Abstract: T-wave morphological analysis on lead V of the surface ECG could successfully differentiate congenital from acquired causes of QT prolongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Until now, the diagnosis of LQTS relies on genetic testing and the Schwartz Score, taking into account ECG and clinical parameters [ 1 ]. Specific ECG parameters (e.g., T-wave morphologies [ 4 ], QT-interval changes upon stress (e.g., epinephrine or treadmill QT-stress test [ 5 , 6 ]) or echocardiographic markers can help to unmask LQTS but still lack relevant diagnostic value [ 7 , 8 , 9 ]. Hence, reasonable simple tests are still lacking, leaving the resting 12-lead ECG as the most essential diagnostic tool for LQTS detection [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the diagnosis of LQTS relies on genetic testing and the Schwartz Score, taking into account ECG and clinical parameters [ 1 ]. Specific ECG parameters (e.g., T-wave morphologies [ 4 ], QT-interval changes upon stress (e.g., epinephrine or treadmill QT-stress test [ 5 , 6 ]) or echocardiographic markers can help to unmask LQTS but still lack relevant diagnostic value [ 7 , 8 , 9 ]. Hence, reasonable simple tests are still lacking, leaving the resting 12-lead ECG as the most essential diagnostic tool for LQTS detection [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 In addition, although previous studies have identified unique ECG features associated with LQTS or its specific genetic subtypes, these features have mostly involved specific, human-selected features of the ECG, such as shape, slope, and overall morphologic characteristics of the T wave. 2,6,7,14 In a step to involve AI, Hermans and colleagues 15 built upon these T wave morphologic studies by developing a machine learning, support-vector model showing that vectorcardiographic parameters from the T wave can improve diagnosis of LQTS with the capacity to distinguish patients with LQTS from genotypenegative family members with an AUC up to 0.901 based on the model used. In contrast, our AI-ECG used unsupervised feature extraction in which an agnostic approach of the complete ECG waveform across all 12 leads of the ECG, as compared with the T wave alone, was analyzed during training, with network feature selection based on minimizing an error function.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although corrected QT (QTc) values exceeding the 99th percentile in men (≥470 milliseconds) or women (≥480 milliseconds) are the thresholds for further evaluation for LQTS as an otherwise incidental finding in ECG-based screening programs, individuals with a QTc greater than or equal to 500 milliseconds are at increased risk of LQTS-associated events. Over the years, in addition to the QTc, several ECG features, such as specific T wave shapes for the LQTS genetic subtypes, 2 QT prolongation on treadmill exercise testing, 3 following epinephrine challenge, 4 or upon brisk standing, 5 as well as novel ECG-or echocardiogram-derived risk factors, such as T wave morphologic characteristics and the electromechanical window, [6][7][8] have improved diagnosis and risk stratification for these patients.…”
mentioning
confidence: 99%
“…Personalized risk stratification for diLQTS is aided by the Pro‐QTc score and Tisdale score diagnostic tools (Haugaa et al, 2013; Schwartz & Woosley, 2016; Tisdale et al, 2013). TWM has also been shown to enhance discrimination of abnormal repolarization in aLQTS (Couderc et al, 2011; Graff et al, 2009; Graff et al, 2010; Heijman & Crijns, 2015; Johannessen et al, 2014; Sugrue et al, 2015; Sugrue, Noseworthy, et al, 2017; Vicente et al, 2015).…”
Section: Introductionmentioning
confidence: 99%